2001
DOI: 10.1086/324082
|View full text |Cite
|
Sign up to set email alerts
|

InvasiveAspergillusStomatitis in Patients with Acute Leukemia: Report of 12 Cases

Abstract: An 8-year retrospective analysis of invasive Aspergillus stomatitis in neutropenic patients with acute leukemia was performed to characterize the epidemiology and clinical features of the infection. Twelve cases of invasive Aspergillus stomatitis were identified with both clinicohistological and microbiological evidence, and the majority of cases were caused by Aspergillus flavus (10 [83%] of 12 patients). The infection was strongly suspected when a neutropenic patient developed persistent fever without a know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…Delayed diagnosis or inappropriate treatment may result in massive tissue destruction and possible extension into the cranial base and/or vault and orbit, via the blood flow, and determine blindness, lethargy, seizure and eventually death [2]. Aspergillosis very rarely arises in healthy individuals and more commonly affects insulin-dependent diabetics with poorly controlled disease, immune-compromised patients [18,28] or leukaemic patients [10,16]. Non-invasive aspergillosis of the maxillary sinus may be associated with extrusion of root canal cements into the sinus, and it has been suggested that zinc oxide-based endodontic materials might promote the infection, as zinc may act as a growth factor for Aspergillus [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed diagnosis or inappropriate treatment may result in massive tissue destruction and possible extension into the cranial base and/or vault and orbit, via the blood flow, and determine blindness, lethargy, seizure and eventually death [2]. Aspergillosis very rarely arises in healthy individuals and more commonly affects insulin-dependent diabetics with poorly controlled disease, immune-compromised patients [18,28] or leukaemic patients [10,16]. Non-invasive aspergillosis of the maxillary sinus may be associated with extrusion of root canal cements into the sinus, and it has been suggested that zinc oxide-based endodontic materials might promote the infection, as zinc may act as a growth factor for Aspergillus [20].…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillosis usually occurs in immune-suppressed or debilitated individuals [31], such as patients with neutropenia [17], leukaemia [10,16,18,30], acquired immunodeficiency syndrome [23,27], cancer [25], treated with corticosteroids or with otherwise imbalanced macrophagic functions [24]. In such instances, inhaled spores [22] invade blood vessels, causing thrombosis and infarction and can erode through the facial planes, cartilagine and bone [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that non-fumigatus Aspergillus spp. [3][4][5][6], including Aspergillus flavus [7,8], are emerging as predominant pathogens in various transplant and cancer centres in the USA and around the world [9][10][11][12][13][14]. Although voriconazole (VCZ) [15,16], the drug of choice for treatment of invasive aspergillosis, has been in use only for the past 3 years, breakthrough infections with Aspergillus and Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…Although voriconazole (VCZ) [15,16], the drug of choice for treatment of invasive aspergillosis, has been in use only for the past 3 years, breakthrough infections with Aspergillus and Candida spp. as well as clinical isolates of A. fumigatus showing reduced susceptibility to VCZ therapy [14] have been reported. Mortality, despite therapy, remains high, and drug resistance might partly account for treatment failures.…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus and other filamentous fungi are uncommon causes of isolated oral lesions and occur almost exclusively in profoundly neutropenic patients [45], similar to invasive aspergillosis at other anatomic sites [46]. Treatment is systemic amphotericin B, and prognosis depends on correction of the underlying immunosuppression, particularly neutrophil recovery.…”
Section: Filamentous Fungimentioning
confidence: 99%